Understanding PROMISE Participant Transition Experiences Using Qualitative Data: Reflections on Accessing Services and Employment Outcomes. (October 2021) - Schlegelmilch, Amanda; Anderson, Catherine A.; Brinck, Emily A.; Roskowski, Matthew; Trainor, Audrey; Hartman, Ellie
Youth with disabilities transitioning from high school to adulthood experience barriers in achieving competitive integrated employment outcomes comparable with peers without disabilities. Promoting Readiness of Minors in Supplemental Security Income (PROMISE) in the state of Wisconsin (WI) serviced 2, 024 youth and families, with 1, 018 accessing services and supports, including, but not limited to, soft skills, self-advocacy, benefits counseling, career counseling, and paid work experiences. This qualitative, multiple case study purposively selected four youth participants and their families to represent one of four categories: engaged and acquired paid employment, engaged and did not acquire paid employment, unengaged but did acquire paid employment, and unengaged and did not acquire paid employment. Results indicated that participants across all four case studies expressed the desire to work and were optimistic about the future resulting from their experience with WI PROMISE. This study will go beyond the results and provide lessons learned and implications for future research.